Campus Asset Management: Optimization of Tangible Assets and Intangible Assets in Improving Higher Education Performance - Mutiarawan, Mutiarawan; Aribowo, Kusworo; Saputra, Asep Dana (Journal of Economics and Social Sciences (JESS), 2026)
Higher education institutions as knowledge-based organizations possess complex asset characteristics, encompassing not only tangible assets such as infrastructure, facilities, and technology, but also intangible assets including human resources, organizational systems, academic culture, and institutional reputation. The main challenge in campus asset management lies in the prevailing administrative-oriented approach that prioritizes physical assets, while intangible assets despite their strategic role in institutional value creation remain insufficiently integrated into asset management practices. This study aims to examine campus asset management through the perspective of integrating tangible and intangible assets to enhance institutional performance, reputation, and competitiveness. The study adopts a qualitative approach using a literature review method, drawing on books, national and international journal articles, and policy documents related to asset management, intellectual capital, and higher education governance. The findings indicate that tangible assets function as foundational enablers for the development of intangible assets, whereas intangible assets serve as key value drivers in achieving sustainable competitive advantage. The integration of both asset types is therefore essential for establishing strategic, sustainable, and value-oriented campus asset management.